Chronic inducible urticaria – having more than one is common and clinically relevant - Lebedkina, Marina; Kovalkova, Elena; Andrenova, Gerelma; Dushkin, Alexander; Chernov, Anton; Nikitina, Ekaterina; Karaulov, Alexander; Lysenko, Maryana; Maurer, Marcus; Kocatürk, Emek; Fomina, Daria (Frontiers in Immunology, 2025)
BackgroundChronic inducible urticaria (CIndU) is characterized by wheals and/or angioedema (AE) for 6 weeks or more in response to specific and definite triggers. Individual patients can have more than one type of CIndU. Reports on this come from single cases or small case series, most epidemiological studies did not assess whether these urticaria are standalone or mixed.ObjectiveDetermine the features of mixed CIndU and how they differ from standalone forms.MethodsIn a prospective cohort study we performed provocative testing in 210 patients with CIndU. A total of 188 patients were included (125 with the standalone CIndU and 63 with the mixed CIndU. Within each group, patients were divided into subgroups: symptomatic dermographism (SD), cold (ColdU) and cholinergic urticaria (CholU).ResultsMixed CIndU most commonly were SD+ColdU (n=19, 30.2%), SD+CholU (n=15, 23.8%), SD+DPU (n=12, 19%) and ColdU+CholU (n=9, 14.3%). Comorbid chronic spontaneous urticaria (CSU) (50.8% vs 20.8, p<0.001) and AE (36.5% vs. 20%, p=0.014) were more common in patients with mixed CIndUs. In patients with mixed CIndUs, their onset time is more closely linked to each other (n=43; 68.2%) as compared to that of comorbid CSU (12 of 32, 37.5%). MixedSD patients are younger, show earlier onset of disease and have higher rates of AE and lower rates of atopic dermatitis (AtD), as compared to patients with standalone SD. MixedColdU patients have higher rates of comorbid CSU and lower rates of AtD, higher levels of total IgE and eosinophils. MixedCholU patients are older, have a high rate of comorbid CSU, a lower incidence of allergic disease.ConclusionThis study shows for the first time that each combinations of mixed CIndU represent a distinct phenotype with its own features. These phenotypes require special attention of specialists.